2013
DOI: 10.1126/science.1237150
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dynamics of Chromosome Translocations in Living Cells

Abstract: Chromosome translocations are a hallmark of cancer cells. We have developed an experimental system to visualize the formation of translocations in living cells and apply it to characterize the spatial and dynamic properties of translocation formation. We demonstrate that translocations form within hours of the occurrence of double-strand breaks (DSBs) and that their formation is cell cycle-independent. Translocations form preferentially between prepositioned genome elements, and perturbation of key factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
296
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(321 citation statements)
references
References 40 publications
21
296
1
3
Order By: Relevance
“…Moreover, the chromosomal translocation in the ES leads to overexpression of the same set of genes that is consistently increased in primary samples from ARTICLE patients. FISH analysis provided an accurate measure of the efficiency of the chromosomal translocations induced by the CRISPR/Cas9 system, and showed that the cell frequencies of chromosomal translocation (Supplementary Table 2) are three to four log-units higher than those obtained with other methods based on nucleases and recombinases 5,6,27 . The method also enjoys the benefits common to other CRISPR-Cas9 techniques, in being cheap, simple, easy and intuitive to design, and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the chromosomal translocation in the ES leads to overexpression of the same set of genes that is consistently increased in primary samples from ARTICLE patients. FISH analysis provided an accurate measure of the efficiency of the chromosomal translocations induced by the CRISPR/Cas9 system, and showed that the cell frequencies of chromosomal translocation (Supplementary Table 2) are three to four log-units higher than those obtained with other methods based on nucleases and recombinases 5,6,27 . The method also enjoys the benefits common to other CRISPR-Cas9 techniques, in being cheap, simple, easy and intuitive to design, and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…In G1 phase of the cell cycle, 53BP1 accumulates at DSBs by binding to dimethylated histone H4 (H4K20me2) (Huyen et al 2004) and DSB-induced ubiquitylated Lys15 of histone H2A (H2AK15Ub) . It results in an increased mobility of the chromatin surrounding the DSBs (Krawczyk et al 2012, Lottersberger et al 2015, although it remains unclear whether this is the case for all DNA breaks in the nucleus (Kruhlak et al 2006, Soutoglou et al 2007, Roukos et al 2013. Additionally, 53BP1 promotes the recruitment of downstream effectors including the replication timing regulatory factor 1 (RIF1) (Chapman et al 2013, EscribanoDiaz et al 2013, Feng et al 2013, Zimmermann et al 2013, pax transactivation domain-interacting protein (PTIP) and MAD2 mitotic arrest deficient-like 2 (MAD2L2) (Boersma et al 2015, Xu et al 2015, which are thought to limit the accessibility of BRCA1 to DSBs, thereby inhibiting DNA end resection.…”
Section: Brca2 Is a Central Mediator Of Dsb Repair By Hrmentioning
confidence: 99%
“…Alteration of genetic information induced by endogenous and exogenous DNA damage in cancer cells has been suggested to lead to the dysregulation of genomic activities including transcription, replication and DNA repair. Recently, chromosomal translocations have been observed in living cells to occur preferentially between genome elements that are in close spatial proximity, 19 highlighting the need to investigate disease-related genome modifications in the context of the cell nucleus. Current and future methods should therefore be applied 1) to understand how nucleome structure and function relate to pathogenesis, especially cancer; and 2) to develop new diagnostic and therapeutic tools.…”
Section: Linking Nucleome Alterations To Disease Phenotypesmentioning
confidence: 99%